VD_FINDINFO ML / 2024 / 141 vom 18. Oktober 2024 - VD Tribunal cantonal (2024)
DÉPENS, DÉFAUTCONTUMACE, RÉPARTITION DES FRAIS | 106 al. 1 CPC (CH), 106 CPC, 95 al. 1 let. b CPC (CH), 95 al. 3 let. b CPC (CH), 3 al. 2 TDC